Original paperThe leukemogenic role of (iASPP) in acute leukemia - Almawgood, Sohier Abdel; Hasan, Nehal Salah; Yousef, Mai (Archives of Medical Science, 2007)
Introduction: The ASPP family (apoptosis – stimulating proteins of p53) comprises three proteins, ASPP1, ASPP2 and iASPP, that interact with and modulate the behavior of p53. ASPP1 and ASPP2 enhance the ability of p53 to induce apoptosis by causing p53 to up regulate the expression of proapoptotic genes specifically rather than genes involved in cell cycle arrest. Inhibitory member of the ASPP family (iASPP) acts as inhibitor for the p53, it was originally identified as a nuclear protein that interacts with and inhibits NFkb p56 RelA and inhibits p53-mediated cell death as well. Material and methods: To examine the role of iASPP in acute leukemic patients, we analyzed iASPP mRNA expression in acute leukemia by semi quantitative reverse transcriptase polymerase chain reaction (RT-PCR). Results: The results showed that the median level of iASPP in acute lymphoblastic leukemia and acute myeloid leukemia patients was significantly higher than those in cells from normal donors (p=0.04). The expression of iASPP in ALL and AML patients was not associated with age, gender, hemoglobin, platelets; blasts count in bone marrow, treatment outcome but was associated with blasts count in peripheral blood and total leucocytic count in AL patients. Conclusions: The results of the present study suggest that iASPP may play a role in leukemogenesis and/or disease progression of acute leukemia.